PERANCANGAN DAN APLIKASI PETA CERITA E-LEARNING MATERI KEBERAGAMAN BUDAYA GLOBAL UNTUK MENINGKATKAN LITERASI DIGITAL SISWA KELAS IV SEKOLAH DASAR - Zumrotul Ngafifah; Cindya Alfi; Mohamad Fatih (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study is to explore ways to improve students' digital literacy skills in elementary schools by utilizing story maps in the online learning process. In designing this e-learning story map, the researcher applied the Research and Development method. The development process follows the ASSURE model, which consists of six stages: student analysis, target determination, selection of methods, media, and materials, implementation of media and materials, encouraging student participation, and finally evaluation and revision. The topic and source of this study were fourth-grade students at SDN Tumpang 02 in Blitar Regency. Interviews, recordings, and surveys from experts in the media and materials sector were used to collect information. Validation is important for the effectiveness of improving digital literacy. The validation process in this development involved two validators representing both fields, resulting in a media expert validator obtaining a percentage of 91% and a material expert validator with a percentage of 97%, and both results are included in the "very valid" category. The result of the increase in digital literacy is 0.8258 which is included in the "High" category.